Inflation Transmission in Greater China. (November 2015) - Liu, Ming‐Hua; Margaritis, Dimitris; Zhang, Yang
Abstract: This paper examines inflation dynamics in Greater China. Using an asymmetric error correction model, we investigate how inflation in Hong Kong and Macao are related to inflation in Chinese Mainland. Our results based on data from July 1997 to December 2012 reveal that a long‐term equilibrium relation exists between inflation in Chinese Mainland and inflation in both Hong Kong and Macao, the two Special Administrative Regions of China. The degree of inflation pass‐through is higher for Macao than for Hong Kong. Moreover, we find no evidence of asymmetries in either Hong Kong and Macao's adjustment speeds towards long‐run equilibrium or in the short‐run pass‐through of accelerating or decelerating inflation in the Mainland. Collectively, our results show a close relationship among price dynamics of the three economies and call for a reconsideration of the exchange rate anchor in the Greater China Region.